2021
DOI: 10.3390/ijerph18189728
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Substance Use and Mental Health Burden among Women during the Second Wave of COVID-19 in Germany

Abstract: Unlike men, who are disproportionately affected by severe disease progression and mortality from COVID-19, women may be more affected by the economic, social and psychological consequences of the pandemic. Psychological distress and mental health problems are general risk factors for increases in the use of alcohol and other substances as a dysfunctional coping mechanism. Methods: An analysis was carried out of the female subset (n = 2153) of a population-based, cross-sectional online survey (October–December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 59 publications
3
9
0
4
Order By: Relevance
“…Feelings of isolation, barriers and disruptions to support, and economic hardship due to the pandemic have contributed to poorer mental health among the wider population [ 135 , 136 , 137 ] and have likely been magnified for PEH, who already experience higher rates of mental health conditions [ 138 ]. These factors, as well as depression and anxiety, have also been associated with changes in substance use during the pandemic [ 139 , 140 , 141 ], findings that were supported by this review. In an effort to minimise risk of virus transmission, many health services shifted toward service provision via telehealth [ 142 , 143 , 144 ].…”
Section: Discussionsupporting
confidence: 78%
“…Feelings of isolation, barriers and disruptions to support, and economic hardship due to the pandemic have contributed to poorer mental health among the wider population [ 135 , 136 , 137 ] and have likely been magnified for PEH, who already experience higher rates of mental health conditions [ 138 ]. These factors, as well as depression and anxiety, have also been associated with changes in substance use during the pandemic [ 139 , 140 , 141 ], findings that were supported by this review. In an effort to minimise risk of virus transmission, many health services shifted toward service provision via telehealth [ 142 , 143 , 144 ].…”
Section: Discussionsupporting
confidence: 78%
“…In a similar way to our results, the study by Schecke et al examined whether legal and illegal psychoactive substance use changed among German women during the COVID-19 pandemic. That survey also showed that the logistic regression for generalized anxiety acted as a significant predictor for increased use of nicotine and other substances ( 12 ). This increase could be a reaction to the stress derived from the pandemic situation, as has previously been demonstrated in the outcomes of other studies researches carried out in Europe ( 34 , 35 ) and the United States ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that anxiety symptoms, sleep disorders, psychological distress and depressive disorders have increased as a response to COVID-19 outbreak. Evidence indicates that there are gender differences in depression, anxiety and sleeplessness due to the pandemic with women experiencing higher depression and anxiety levels than men ( 10 12 ). Gender is an important determinant of mental health and the management of it in health services.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from Italy and Belgium reported that increased alcohol consumption was particularly prevalent in men [16,17]. Among women in Germany, 23% increased their alcohol consumption during the COVID-19 pandemic, and the presence of generalized anxiety was a significant predictor of increases in alcohol use [18]. Another study from Germany reported that consuming more alcohol during lockdown was associated with middle age, higher subjective stress due to the COVID-19 pandemic, a lower agreement with the importance of the restrictions, and consuming alcohol more than once per week before the lockdown [19].…”
Section: Introductionmentioning
confidence: 95%